Calcium-activated potassium channels in ischemia reperfusion: a brief update - Tano, Jean-Yves; Gollasch, Maik (Frontiers in Physiology, 2014)
Ischemia and reperfusion (IR) injury constitutes one of the major causes of cardiovascular morbidity and mortality. The discovery of new therapies to block/mediate the effects of IR is therefore an important goal in the biomedical sciences. Dysfunction associated with IR involves modification of calcium-activated potassium channels (KCa) through different mechanisms, which are still under study. Respectively, the KCa family, major contributors to plasma membrane calcium influx in cells and essential players in the regulation of the vascular tone are interesting candidates. This family is divided into two groups including the large conductance (BKCa) and the small/intermediate conductance (SKCa/IKCa) K+ channels. In the heart and brain, these channels have been described to offer protection against IR injury. BKCa and SKCa channels deserve special attention since new data demonstrate that these channels are also expressed in mitochondria. More studies are however needed to fully determine their potential use as therapeutic targets.